The methods and baseline characteristics of a multi-site randomized controlled trial evaluating mindfulness-based relapse prevention in conjunction with peer support to improve adherence to medications for opioid use disorders - Mumba, Mercy Ngosa; Mugoya, George Tongi; Allen, Rebecca S.; Glenn, Andrea L.; Richman, Joshua; Ghera, Anchal; Butler, Austin; Rogers, Blossom; Granger, Teresa Ann; Davis, Lori L. (Frontiers in Psychiatry, 2024)
Introduction: Medications for opioid use disorders (MOUD) remain the gold standard for treating OUD, but treatment initiation and adherence remain challenging. Exclusive utilization of pharmacotherapy as a treatment modality for OUD is sub-optimal, and a combination of psychotherapies and pharmacotherapies is recommended. General trends indicate the benefits of peer mentoring and MBRP separately. Therefore, we hypothesize that the combined effect of MBRP and Peer mentoring will produce synergistic improvements in MOUD adherence compared to an enhanced twelve-step facilitation (TSF).Methods: This paper describes the methods and baseline characteristics of a multi-site randomized controlled trial evaluating the effectiveness of a combination of MBRP and peer support (MiMP) compared to an enhanced TSF in improving adherence to MOUD. Both MiMP and TSF are 12-week manualized protocols that utilize licensed therapists. The interventions are delivered in weekly group sessions that last about 75-90 minutes per session. The primary outcome is MOUD adherence. Secondary and exploratory outcomes include relapse, cravings, depression, anxiety, stress, quality of life, and pain catastrophizing.The participants' ages ranged from 21 years to 77 years, with a mean age of 44.5 (SD ± 11.5 years). There was an almost equal distribution of gender and place of residence. Overall, 51.9% (n=54) of participants identified as female and 48.1% (n=50) were male. Similarly, 51.9% (n=54) of participants resided in urban areas, while 48.1% (n=50) resided in rural areas.Participants identified as either black or white, with over three-quarters identifying as white (77.9%, n= 81) and 22.1% (n= 23) as black. Most participants randomized to the 12-step facilitation group were white (93.1%). Relationships and employment status were well distributed between categories. Over half of the participants reported some college or higher education. Over 90% of the participants made less than $75,000 per year. Some participants indicated that they had both public and private health insurance.This study is innovative in several ways including combining MBRP and peer support, addressing comorbid mental health issues among individuals with OUD, utilizing manualized protocols, and evaluating of both physiological and self-reported measures in assessing cortisol reactivity as a predictor of relapse and treatment outcomes.